2022
DOI: 10.1097/fjc.0000000000001192
|View full text |Cite
|
Sign up to set email alerts
|

Safety and Efficacy of Periprocedural Bridging With Cangrelor Versus Eptifibatide

Abstract: :Patients with percutaneous coronary interventions undergoing procedures often require interruptions in their dual antiplatelet therapy. Periprocedural bridging is considered for patients at high thrombotic risk using intravenous cangrelor, a reversible P2Y12 inhibitor with a short half-life, or eptifibatide, a glycoprotein IIb/IIIa inhibitor, with a slightly longer half-life but less costly alternative. This study aims to assess the safety and efficacy of cangrelor compared with eptifibatide when used in a pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 13 publications
0
11
0
Order By: Relevance
“…8 Retrospective studies of cangrelor bridging for NCS report either no bleeding or minor procedural bleeding (Table 4), suggesting that this is a safe approach to perioperative platelet inhibition. [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27]…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…8 Retrospective studies of cangrelor bridging for NCS report either no bleeding or minor procedural bleeding (Table 4), suggesting that this is a safe approach to perioperative platelet inhibition. [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27]…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, the BRIDGE trial reported a low incidence of preoperative ischemic events, and retrospective studies of cangrelor bridging for NCS report a low incidence of perioperative MACE (Table 4). 8,[13][14][15][16][17][18][19][20][21][22][23][24][25][26][27] Thus, cangrelor bridging appears to be an effective approach for mitigating the risk of perioperative MACE.…”
Section: Table 4 (Continued)mentioning
confidence: 99%
See 1 more Smart Citation
“…It should be considered in patients with renal insufficiency, as clearance of eptifibatide is influenced by renal function [ 98 ]. Moreover, a study by Yun et al from 2019 showed that cangrelor and eptifibatide were similar in terms of overall bleeding events and major inpatient cardiac adverse events [ 100 ].…”
Section: Eptifibatidementioning
confidence: 99%
“…A study comparing cangrelor and eptifibatide discovered that both drugs have comparable safety and efficacy as a bridge treatment for patients with recent coronary stents. Additionally, substituting cangrelor with eptifibatide in select patients could result in cost savings [ 51 ].…”
Section: Reviewmentioning
confidence: 99%